Follicular Development of Aged Rats Ovarian Injected Human Umbilical Cord Mesenchymal Stem Cells - Resti Rahma Dianti; Alif Iman Fitrianto; Adkhilni Utami; Wining Astini; Adisti Dwijayanti; Frans Dhyanagiri Suyatna; Kelvin Yaprianto; Indra Bachtiar; Aryani Sismin Satyaningtijas; Adi Winarto; Arief Boediono (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2020)
Female reproductive system showing the fastest signs of aging. The ovarian aging characterized by a decrease in follicular development. Stem cells are undifferentiated cells and can form a variety of different cells as the foundation of tissues and organs. Previous studies reported that Bone Marrow Mesenchymal Stem Cells (BM-MSCs) transplantation can restore follicular development in damaged ovarian rats. This study aimed to analyze the number of follicular development in aged rats and to analyze the capability of human Umbilical Cord Mesenchymal Stem Cells (hUC-MSCs) to improving follicular development in aged rats. This study used 3 mature rats (4 months old), and 9 nine aged rats (22-24 months old), Spraque Dawley (SD) strain. They were divided into four groups. The first and the second group was mature rats and aged rats without injection. The third and the fourth group was aged rats injected hUC-MSCs dose 106 cells/kgBW and hUC-MSCs dose 107 cells/kgBW. The injection carried out 4 times at 3-month intervals. The parameters observed were follicular development and homing image of hUC-MSCs in ovarian tissue. The results showed that the number of follicular developments in aged rats 22-24 months decreased significantly compared to mature rats 4 months old. Injection of hUC-MSCs at dose 106 cells/kgBW and 107 cells/kgBW did not increase follicular development in aged rats. hUC-MSCs did not found in ovarian tissue. It could be concluded that aged rats 22-24 months old no longer productive indicated from the number of follicular developments and corpus luteum decreased. The injection of hUC-MSCs intravenously did not indicate an improvement of follicular development in aged rats 22-24 months old.